Concept and evolvement of Chinese Contract Law - Jacobs, Faizel (Department of Commercial Law, 2016)
This dissertation discusses the evolvement of Chinese Contractual law and establishes as to whether it converges or has any similarity with any Western legal norms and standards. I will view the recent history and early sources of Chinese law as influenced by political changes and tradition; as well as the influence of international commercial transaction agreements. The formation of a contract, standard terms and modification of contracts and the dissolution and breach in Chinese contracts will be discussed and also whether parties do in fact have the freedom to enter agreements with each other without third party interference. The role played by the Judiciary when addressing the issue of contractual disputes and in particular the Interpretations and Opinions of the Supreme Peoples' Court of China on the new Chinese Contract Law will be considered, as well as whether the concept of Doctrine of Precedent as practiced in the West does in fact exist in China. My motivation for choosing this topic is based on the fact that China is (1) the second largest economy in the world and her consequential impact on world trade, (2) its economic influence in the world especially Africa, (3) the fact that China is South Africa's largest trade partner, (4) South Africa's membership of BRICS [1] , and (5), China's growing influence in the world in the creation of parallel institutions to the West, such as the New Development Bank (formerly known as the BRICS Development Bank) rivalling current Western institutions such as the World Bank and the International Monetary Fund.